Ecological dynamics of wolves and their ungulate prey in Yellowstone National Park - Leedham, O (2023)
A core challenge for ecologists is to understand how biotic and abiotic processes influence demography and the dynamics of populations through time. I explore how ageing, social processes, and population conditions drive demography, movement, and community dynamics in a restored population of wolves Canis lupus in Yellowstone National Park, USA. I combine the analysis of empirical data for multiple species with models designed to simulate the dynamics of the system in which they live and interact, focussing on social and demographic processes in wolves.